Incidence and occurrence of academic burnout: The impact of personality, self-efficacy and self-esteem and post-pandemic effects - Morando, Martina; Smeriglio, Rossana; Maggio, Claudio; Di Nuovo, Santo; Platania, Silvia (Environment and Social Psychology, 2023)
Academic burnout is a health issues that largely interests the global community and troubles students at all academic levels. Despite the significant effects on students’ quality of life, well-being, and academic performance, yet, it has not been adequately examined. Therefore, this study is aimed at exploring the levels of academic burnout, the personality’s role as predictor (through Big Five Factors) and the effect of protective factor like self-efficacy and self-esteem. Moreover, in an innovative way, a multi-group analysis will be proposed to verify differences between the variables observed in the COVID-19 and post-COVID-19 period. Through a total sample of 609 students, it proposed a multiple-mediation model with a comparison between two phases: pandemic and post-pandemic. Results suggest that among the Big Five Factors, there are strong predictors of the effects of burnout, and specifically that conscientiousness and self-efficacy are important in the management of the academic burnout and that self-esteem could support students and mitigate feelings of inadequacy in different academic challenges. Moreover, the pandemic seems to have worsened emotional instability and negative effect on university stress. Studies such as this provide valuable information for educators and all stakeholders who want to contribute to the education and training for students’ life and educational journey in a way that is certainly more holistic, equitable and accessible to all.